Arquitectura wormhole aplicada a robôs móveis - Cruchinho, Gonçalo Manuel (2012)
The use of robots is becoming more widespread, focusing more on the areas of exploration, security and entertainment. With the introduction of team, the robots show an increase of productivity in their tasks, enabling them to do more in less time, although with that addition, some problems may occur. Those problems are due to the introduction of the communicational component necessary to the team, which can cause delay in the tasks that the robot performs, due to the necessity of external values provided by other robots and due to the unbounded delay that exists when getting those values. To mitigate the problem indicated above, a middleware was created that guaranties the timely control of virtual robots. That middleware was created using the wormhole architecture, which defines two components, one simple and another complex, both capable of controlling the robot. The simple component guaranties the synchronous execution property, which can be used by the complex component. The complex component tries, when possible, to control the robot while the simple component only tries to control it when the complex component can?t. This project makes use of the middleware identified previously, having the objective of improving the middleware?s modules, getting it ready to port to the physical robot and validating the resulting solution in order to check if it can control the robot within a known interval of time after the failure of one components. With this port we want to verify that this architecture serves correctly the purpose of controlling a robot. The results enable us to conclude that the wormhole architecture, when applied to a robot, mitigates the effects of the introduction of communication in the robot, due to the fact that if there is delay in the control it is possible to the simple component to maintain the temporary control of the robot. This delay mitigation applies itself to other type of delay like asynchronous interruptions that affect the complex component.